Thai Youth's Leadership Code: Characteristics of Leadership from the Perspective of Thai Youth (European Journal of Social Sciences, 2022)
The purpose of this study were: 1) to define the characteristics of leadership from the perspective of Thai Youth and 2) to investigate the Thai Youth Leadership Code by using Leadership Code Model. This study is qualitative research using Descriptive Methodology. The informants of the study are 16 Thai youth leaders (15 – 24 years old) who had participated in any oversea high school exchange student program to represent group identity. The data was collected by in-depth interview using key questions to define physical traits, style, situation, competencies, results, and brand of leadership. Data was analyzed following the Leadership Code Model which have 5 rules of leadership and 2 dimensions of time and attention. The findings indicated that Leadership from youths perspectives can be classified as Personal Proficiency, Executor and Strategist respectively. The context of time has been found in Near-term operational dimension and the context of attention has been found in Organization dimension. Youths Leadership prioritizes developing themselves first while the meaning of the organization is their society. In conclusion, this study found that the Leadership Code Model is the decent baseline for organizational leadership study rather than society, and is incomplete for youths leadership evaluation. The recommendation is to conceptualize Youths Leadership Code Model that is appropriate for youths leadership study.